Thin Film Biosynthesis of Zinc Oxide Nanoparticles Using Thymus Serpyllum Plant Extract - Saleh, Rasha Hosam (Journal of natural sciences, life and applied sciences, 2024)
Thin films of zinc oxide nanoparticles were made in this work with a Thymus serpyllum plant ex-tract. After the plant was gathered and thoroughly cleaned, a set of procedures was followed to make the plant extract. Next, one of the zinc compounds and the plant extract were used in a pro-cess that was shown to produce zinc oxide nanoparticles. Using infrared radiation, scanning elec-tron microscopy, and X-ray diffraction, the resultant nanocomposite was discovered and de-scribed. The findings demonstrated that the nanoparticles were layered and ranged in size from 20.29 to 65.30 nm.
Keywords: Silver Nanoparticles; Thymus Serpyllum Plant; Biosynthesis; Green chemistry